The Supervisory jurisdiction of the constitutional judiciary and its role in protecting rights and freedoms - Mohammad Alatraqchy; Nashwaan ِAli (الرافدین للحقوق, 2022)
The supervisory jurisdiction is considered one of the constitutional judiciary's most prominent and important functions. Some jurisprudential perspectives even point to the necessity of limiting the function of the constitutional judiciary to this supervisory role.This could be understandable, especially since this supervisory role achieves effective protection of rights and freedoms, whether it is in the form of oversight over the constitutionality of laws and regulations, or in the form of oversight over the ‘omission’ or ‘deviation’ of the legislation. Undoubtedly, the achievements of the constitutional judiciary in this regard is clearly noticeable; especially, its  approaches to addressing the problem of ‘unconstitutionality of the legislations’. Whether exercised through the constitutional oversight over the legislation that are ‘unconstitutional’ or the oversight that is performed over the ‘omission’ or ‘deviation’ of the legislative powers.   In the final analysis,  the constitution is the source  of the rights and freedoms that all authorities must respect,  and for which the principle of the supremacy of the constitution guarantees formal and objective immunity from violation.